The electric structure of the schizosphere in SE Thessaly, Greece, and its correlation with active tectonics - Tzanis, A.; Drosopoulou, E. (Bulletin of the Geological Society of Greece, 2007)
We report the results of a magnetotelluric study in SE Thessaly, Greece, and their correlation with the active tectonics of the area. The data comprised 14 wide-band (150-0.005 Hz) soundings performed in the periphery of the cities of Volos, Velestino and N. Anghialos. The spatial analysis of the MT impedance tensor shows a transition from a shallow (< 1 km) geoelectric structure associated with apparent local structural features, to the deeper (> 3 km) schizosphere associated with large scale structures with ESE-WNW to SE -NW orientation. Quantitative interpretation was carried out with 2-D inversion and yielded high quality images of the geoelectric structure at depths 3-15 km; this depth range corresponds to the seismogenic layer. Conductive structures in the general E-W direction could be detected and correlated with neotectonic faults. In addition, a possible relic of the now extinct Mikrothivai volcano (1.5±0.1 Ma BCE) has been identified. Within the seismogenic layer the spatial MT data correlate almost exactly with the stress field calculated by inversion of focal mechanisms from local earthquakes and appear to provide an electrical image of the transition from the dextral NE-SW transformation associated with the N. Aegean trench to approximately N-S extension in the study area